Islamic Finance in Sub-Saharan Africa : Status and Prospects - Gelbard, Enrique (IMF Working Papers; Working Paper ;, 2014)
Islamic finance is a fast growing activity in world markets. This paper provides a survey on Islamic Finance in SSA. Ongoing activities include Islamic banking, sukuk issuances (to finance infrastructure projects), Takaful (insurance), and microfinance. While not yet significant in most Sub-Saharan countries, several features make Islamic finance instruments relevant to the region, in particular the ability to foster SMEs and micro-credit activtities. As a first step, policy makers could introduce Islamic financing windows within the conventional system and facilitate sukuk issuance to tap foreign investors. The entrance of full-fleged Islamic banks require addressing systemic issues, and adapting the crisis management and resolution frameworks. The IMF can play a role by sharing international experiences and providing advice on supervisory and regulatory frameworks as needed.